2017
DOI: 10.11607/prd.3109
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Clinical and Radiographic Assessment of Platform-Switched Laser-Microchannel Implants Placed in Limited Interimplant Spaces

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Laser-Lok is a computer-controlled laser ablation technique, which creates an implant neck with precision-engineered cell-sized microchannels (size 8 μm). It has been demonstrated that this treatment induces a fibroblast growth that leads to a stable connective tissue attachment, providing an epithelial barrier during initial healing phases [ 17 , 18 , 19 ]. Histological studies confirmed the possibility of achieving a physical connective tissue attachment to the cell-sized microchannel collar of a dental implant [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Laser-Lok is a computer-controlled laser ablation technique, which creates an implant neck with precision-engineered cell-sized microchannels (size 8 μm). It has been demonstrated that this treatment induces a fibroblast growth that leads to a stable connective tissue attachment, providing an epithelial barrier during initial healing phases [ 17 , 18 , 19 ]. Histological studies confirmed the possibility of achieving a physical connective tissue attachment to the cell-sized microchannel collar of a dental implant [ 20 ].…”
Section: Introductionmentioning
confidence: 99%